If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7(x-5)+14=-7
We simplify the equation to the form, which is simple to understand
7(x-5)+14=-7
Reorder the terms in parentheses
+(+7x-35)+14=-7
Remove unnecessary parentheses
+7x-35+14=-7
We move all terms containing x to the left and all other terms to the right.
+7x=-7+35-14
We simplify left and right side of the equation.
+7x=+14
We divide both sides of the equation by 7 to get x.
x=2
| 6x+3=8x-3x | | 12t^2+32t=12 | | 1/2y=1.5 | | 2n/5=30 | | 3z+5z-2=0 | | 261=195-u | | 3x^5-39x^3+108x=0 | | 4x-3/1-6x=x-7/x+9 | | 7x+5=2x+85 | | 3x^3+10x^2-27x=10 | | 5x+51=7x-7 | | 12y^2-41y=-35 | | 2n*5=30 | | 2x+9=10x+20 | | y^2+y=90 | | 2/3y=5 | | 2y+1/15 | | 20x^3+51x^2+27x=0 | | 4x+5/3x+2=x-10/x-8 | | 8x^3y^2-6x^2y^3+2xy^2= | | 7-9x=76-30x | | 2n+10=16 | | 6y-2=7y-2y | | 2y^2-6y-11= | | 2psq+5p=8 | | X^3+10x^2+17x=28 | | x+2/x-3=x-1/x+9 | | 40-5x=4x+20 | | 9x/x-3=54/x+7 | | log(x^2-6x)-log(x)= | | 8xsq-4x=24 | | 1.95y=y+10+1 |